ANALYSIS OF THE INFLUENCE OF TOURISM INDICATORS ON GROSS REGIONAL DOMESTIC PRODUCT IN PROBOLINGGO REGENCY, PASURUAN REGENCY, MOJOKERTO REGENCY, LUMAJANG REGENCY, JEMBER REGENCY AND BANYUWANGI REGENCY - Mochammad Bastomi; Riko Setya Wijaya (SEAN Institute, 2023)
This research aims to analyze the influence of the number of touristattractions, number of hotels, number of restaurants and number of visitors totourist attractions on gross regional domestic product in ProbolinggoRegency, Pasuruan Regency, Mojokerto Regency, Lumajang Regency, JemberRegency and Banyuwangi Regency in a 10-year period. years starting from2012 to 2021. The results of this research show that the number of touristattractions and the number of hotels do not have a significant effect on grossregional domestic product in Probolinggo Regency, Pasuruan Regency,Mojokerto Regency, Lumajang Regency, Jember Regency and BanyuwangiRegency, while the number restaurants and the number of visitors to touristattractions have a positive and significant effect on gross regional domesticproduct in Probolinggo Regency, Pasuruan Regency, Mojokerto Regency,Lumajang Regency, Jember Regency and Banyuwangi Regency. Allindependent variables simultaneously influence regional gross domesticproduct in Probolinggo Regency, Pasuruan Regency, Mojokerto Regency,Lumajang Regency, Jember Regency and Banyuwangi Regency